OP0252 NEUROPATHIES IN SYSTEMIC LUPUS ERYTHEMATOSUS: RESULTS FROM AN INTERNATIONAL, INCEPTION COHORT STUDY. (June 2019) - Hanly, John; Qiuju, LI; Su, LI; Urowitz, Murray B; Gordon, Caroline; Bae, Sang-Cheol; Romero-Diaz, Juanita; Sanchez-Guerrero, Jorge; Bernatsky, Sasha; Clarke, Ann E; Wallace, Daniel J; Isenberg, David; et al.
Abstract : Background: Central nervous system (CNS) involvement accounts for over 90% of neuropsychiatric (NP) events compared to involvement of the peripheral nervous system (PNS) which accounts for most of the other events. Although there is a large body of work on CNS disease in SLE patients, involvement of the PNS is less well established. Objectives: In a multi-ethnic/racial, prospective SLE inception cohort, to determine the clinical characteristics, associations and outcomes in different types of peripheral nervous system (PNS) disease. Methods: Patients were evaluated annually for 19 NP events including seven types of PNS disease. Standardized case definitions and attribution models for each type of PNS event were used. SLE disease activity (SLEDAI-2K), organ damage (SLICC/ACR damage index), autoantibodies, patient (SF-36) and physician (Likert score) assessment of outcome were measured. Time to event and linear regressions were used as appropriate. Results: Of 1, 827 SLE patients, 88.8% were female, 48.8% Caucasian. The mean±SD age was 35.1±13.3 years, disease duration at enrollment 5.6±4.2 months and follow-up 7.6±4.6 years. There were 161 PNS events in 139/1, 827 (7.6%) patients. The predominant events were peripheral neuropathy [66/161 (41.0%)], mononeuropathy [44/161 (27.3%)] and cranial neuropathy [39/161 (24.2%)] and the majority were attributed to SLE. Multivariate Cox regressions suggested longer time to resolution in patients with prior history of neuropathy, older age at SLE diagnosis, higher SLEDAI-2K scores, and for peripheral neuropathy versus other neuropathies. Neuropathy was associated with significantly lower SF-36 physical and mental component summary scores versus patients without NP events. By physician assessment, the majority of neuropathies resolved or improved over time and this was associated with improvements in SF-36 summary scores for peripheral neuropathy and mononeuropathy. Conclusion: PNS disease is an important component of total NPSLE and has a significant negative impact on health related quality of life. The outcome is favourable for most patients, but several factors associated with longer time to resolution were identified. Disclosure of Interests: John Hanly Consultant for: Eli Lilly Canada, Qiuju Li: None declared, Li Su: None declared, Murray B Urowitz Grant/research support from: GSK, Consultant for: BMS, Celgene, GSK, Lilly, UCB, Caroline Gordon Grant/research support from: Sandwell and West Birmingham Hospitals NHS Trust have received funding from UCB to support research work done by my research group that was unrelated to any pharmaceutical product or clinical trial., Consultant for: I have provided consultancy advice and taken part in scientific advisory boards on the design and analysis of clinical trials and the management of lupus for GSK, EMD Serono and UCB. I have taken part in adjudication and safety monitoring committees for BMS., Speakers bureau: I have been paid by UCB for speaking at meetings., Sang-Cheol Bae: None declared, Juanita Romero-Diaz: None declared, Jorge Sanchez-Guerrero: None declared, Sasha Bernatsky: None declared, Ann E Clarke: None declared, Daniel J Wallace: None declared, David Isenberg: None declared, Anisur Rahman: None declared, Joan T Merrill Grant/research support from: Genentech, UCB, GSK, EMD Serono, Pfizer, Celgene, Exagen, Bristol Myers Squibb, Medimmune/Astra Zeneca, Lilly, Amgen, Xencor, Neovacs, Consultant for: Genentech, UCB, GSK, EMD Serono, Pfizer, RemeGen, Celgene, Exagen, Bristol Myers Squibb, Medimmune/Astra Zeneca, Lilly, Immupharma, Amgen, Janssen, Sanofi, Neovacs, Anthera, Speakers bureau: UCB, GSK, EMD Serono, Bristol Myers Squibb, Medimmune/Astra Zeneca, Janssen, Paul Fortin: None declared, Dafna D Gladman Grant/research support from: AbbVie, Amgen, Celgene, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead, Janssen, Lilly, Novartis, Pfizer, and UCB, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GlaxoSmithKline, Consultant for: AstraZeneca, Eli Lilly, GlaxoSmithKline, ILTOO Pharma, MedImmune, Merck Serono, Speakers bureau: GlaxoSmithKline, UCB Pharma, Michelle A Petri Shareholder of: Pfizer, Merck, Grant/research support from: AstraZeneca, Exagen, Consultant for: Eli Lilly, GSK, Merck EMD Serono, Janssen, Amgen, Novartis, Quintiles, Exagen, Inova Diagnostics, AstraZeneca, Blackrock, Glenmark, UCB, and the Annenberg Center for Health Sciences, Ellen M Ginzler: None declared, M.A. Dooley: None declared, Kristjan Steinsson: None declared, Rosalind Ramsey-Goldman: None declared, Asad A Zoma: None declared, Susan Manzi: None declared, Ola Nived: None declared, Andreas Jonsen: None declared, Munther Khamashta: None declared, Graciela S Alarcon: None declared, Ronald F van Vollenhoven: None declared, Elisabet Svenungsson: None declared, Cynthia Aranow: None declared, Meggan Mackay: None declared, Guillermo Ruiz-Irastorza: None declared, Manuel Ramos-Casals: None declared, S. Sam Lim: None declared, Murat Inanc: None declared, Kenneth C Kalunian: None declared, Soren Jacobsen: None declared, Christine Peschken Consultant for: AstraZeneca, Diane L Kamen: None declared, Anca Askanase: None declared, Chris Theriault: None declared, Vernon Farewell: None declared